The phenomenon of yoga in the imagination of Turkish nursing students: "The way to place goodness in the heart" - Özüm Erki̇n; Aynur Çeti̇nkaya; Begüm Güler (BMC, 2024)
Abstract Background The aim of the research is to shed light on the experiences of a group of nursing students enrolled in a yoga elective course who practiced yoga regularly for 14 weeks, regarding yoga and the phenomenon of doing yoga, with a qualitative approach. Methods This qualitative study was conducted at a public university in Izmir, Turkey. The study sample consisted of 61 students enrolled in the 1st-year yoga course at the Department of Nursing, Faculty of Health Sciences. Except for two students, 59 of them participated in the study. Participants attended a face-to-face yoga course once a week for 1.5 h over a 14-week period. Each session comprised 30 min of theoretical instruction and 60 min of practice. In data collection, an interview form containing five questions was used to understand nursing students' experiences and thoughts about practicing yoga. In addition, A4 sized papers in different colors were presented to the participants. The participants were asked to draw and/or cut a shape by choosing the paper in the color that most evokes yoga. Then they were asked to explain why they chose this color and why they drew this shape. Participants were given one hour. After the data were collected, the pictures drawn by the participants and their descriptions of their drawings were transferred to the computer and included in the analysis. Qualitative data were hand-coded by the researchers. Within in-vivo coding, code names were formed from the participants' expressions. The findings analyzed by content analysis were interpreted with the literature under the themes by presenting quotations. Results It was determined that the participants used nature figures (sun, cloud, tree, sky, flower) (f = 75), people doing yoga (f = 12), and sound, light and other figures (bird sound, wave sound, candle, light bulb, traffic light, heart, eye, left key, peace, swing, India, circle, etc.) (f = 29) in the shapes they drew and cut out on A4 sized papers in different colors to describe their experiences and thoughts about practicing yoga. The participants mostly chose blue-green-yellow colors (n = 41). With qualitative question analysis, a list of codes was created from the answers given by the students to the questions for the phenomenon of "doing yoga" (number of codes = 98). After the analysis of the data, four categories were reached. The category names and frequency numbers explaining the phenomenon of practicing yoga were distributed as "symbol of health and serenity (f = 345)", "the way to place goodness in your heart (f = 110)", "the most effective way to meet the self (f = 93)" and "no guarantee of relaxation (f = 71)", respectively. Conclusions The results indicate that yoga is perceived by nursing students as a multifaceted practice that evokes a range of emotional and physical responses. Most participants associate yoga with symbols of health, serenity, and self-awareness, often using natural elements and blue-green-yellow the colors to represent these feelings. However, there is also recognition that yoga may not guarantee relaxation for everyone, as some students reported difficulties in meditation, physical discomfort, and challenges in focusing. The study highlights the variability in how individuals experience yoga, emphasizing both its positive effects on well-being and the potential challenges in practice. These findings suggest that while yoga is widely valued for its calming and health-promoting benefits, it may not be universally effective in achieving relaxation or mindfulness.